2007
DOI: 10.1007/s00266-007-0025-3
|View full text |Cite
|
Sign up to set email alerts
|

Anatomically Shaped Breast Prosthesis in Vivo: A Change of Dimension?

Abstract: The results show that both the round and the anatomically shaped silicone prostheses in vivo largely maintain their original in vitro configuration after subpectoral implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In a previous study, we showed, with the use of a 3D magnetic resonance imaging (MRI) technique, that the in vitro 3D configuration of the round and anatomically shaped silicone gel-filled breast prostheses will hardly change in vivo after subpectoral augmentation [20]. This offers opportunities for preoperative determination of what prosthesis shape to use in a certain type of breast.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we showed, with the use of a 3D magnetic resonance imaging (MRI) technique, that the in vitro 3D configuration of the round and anatomically shaped silicone gel-filled breast prostheses will hardly change in vivo after subpectoral augmentation [20]. This offers opportunities for preoperative determination of what prosthesis shape to use in a certain type of breast.…”
Section: Discussionmentioning
confidence: 99%
“…4 Variables such as type of incision, plane of insertion of the implant, and implant characteristics have previously been addressed in the literature. [5][6][7] In cosmetic surgery, silicon implant breast augmentation is the leading procedure as toxic injectable like liquid silica and polyacrylamide were banned. [8][9][10][11] Ideal shape and size of breast varies according to cultural and individual preferences.…”
Section: Introductionmentioning
confidence: 99%